دور تعليم التفكير الناقد ومهاراته في تجويد العملية التربوية - بروال مختار (جامعة الوادي - University of Eloued, 2021)
نهدف من خلال هذه الدراسة النظرية إلى بيان دور وأهمية أو محورية التفكير الناقد في بناء شخصية المتعلم وضرورة استهدافه عند صياغة المناهج الدراسية ومضامينها باعتباره –أي التفكير الناقد- أساس أي إصلاح ورغبة جادة وحقيقية لتجويد التعليم المدرسي ، ذلك أن إصلاح الواقع والنهوض بالمجتمع وتطويره لن يكون بدون عقلية نقدية مبصرة لمواطن الخلل ومواطن القوة فتعمل على إصلاح الخلل وتقوية عوامل القوة. لذلك سنحاول من خلال هذه الورقة بيان: ما الذي نعنيه بالتفكير النقدي أو الناقد؟ ما هي أوجه ضرورته ومبررات اهتمام المنظومات العالمية للتعليم والتربية به؟ ما هي معاييره وشروطه؟ كيف يمكن للمدرسة والمعلم أن يكسبان المتعلم مهارات التفكير الناقد؟ وغيرها من الأسئلة ذات الصلة بهذا الموضوع الهام.We aim through this theoretical study to clarify the role, the importance, or centrality of critical thinking in building the personality of the learner and the importance to target him, when formulating school curriculums and their contents as it - critical thinking - is the basis of any reform and serious desire to improve school education. So that the reform of reality and the advancement and development of society would not be, without an attentive critical mindset for the weaknesses and strengths, it works to fix the defects and strengthen the factors of strength. Therefore, we will try through this paper to clarify: What do we mean by critical thinking? What are the aspects of its necessity and justifications for the interest of global education and education systems in it? What are its standards and conditions? How can the school and the teacher provide the learner with critical thinking skills? and other questions which related to this important topic
The role of critical thinking education and its skills in improving the educational process
مقال
Keywords: التفكير ، جودة التربية ، التفكير الناقد; thinking, education quality, critical thinking